Pulmonary Artery Sling Presenting as Pneumonia and Inhalation of a Foreign Body - Shujuan Luo; Huaping Rao (Case Reports in Infectious Diseases)
Pulmonary artery sling is a rare cause of respiratory distress created by compression of the lower trachea and right mainstem bronchus due to an aberrant origin of the left pulmonary artery. The condition is frequently associated with recurrent respiratory infections and other congenital malformations including tracheal rings. We present the case of an infant presenting with pulmonary distress and a history of recurrent respiratory infection. The infant underwent surgery to remove a foreign object; however, the symptoms did not resolve. Bronchoscopy revealed bronchus stenosis, and subsequent echocardiogram and CT scans revealed the presence of a pulmonary artery sling. We prescribed infection prophylaxis with the immunomodulator OM-85 to mitigate the risk of further infections prior to surgery. PAS and bronchus stenosis were corrected successfully by surgical intervention leading to resolution of symptoms of respiratory distress and a reduction in the incidence of respiratory infection.